2022
DOI: 10.14202/vetworld.2022.2754-2759
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of RNA viral nucleic acid-based detection of avian influenza virus, Newcastle disease virus, and African horse sickness virus on flinders technology associates card using conventional reverse-transcription polymerase chain reaction

Abstract: Background and Aim: The flinders technology associates (FTA) card is a cotton-based cellulose membrane impregnated with a chaotropic agent that inactivates infectious microorganisms, lyses cellular material, and fixes DNA and/or RNA within the fiber matrix. However, little is known about the effectiveness of these cards for detecting RNA viruses in animals. This study aimed to evaluate the sensitivity of RNA virus detection using conventional reverse-transcription polymerase chain reaction (RT-PCR) on FTA card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(21 reference statements)
0
0
0
Order By: Relevance
“…In contrast, our study detected varying levels of NDV RNA, with 2.83 log 10 ELD 50 detected after the infected card was kept at room temperature for 1 week, increasing to 5.83 log 10 ELD 50 for up to 5 months. Additionally, our study confirmed virus inactivation on the card within 30 min, consistent with reports by Rattanamas et al [46] and Perozo et al [48]. FTA cards unequivocally prove themselves to be suitable for collecting and transporting NDV-positive samples, providing a reliable source of RNA for molecular characterization, and ensuring sample safety.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, our study detected varying levels of NDV RNA, with 2.83 log 10 ELD 50 detected after the infected card was kept at room temperature for 1 week, increasing to 5.83 log 10 ELD 50 for up to 5 months. Additionally, our study confirmed virus inactivation on the card within 30 min, consistent with reports by Rattanamas et al [46] and Perozo et al [48]. FTA cards unequivocally prove themselves to be suitable for collecting and transporting NDV-positive samples, providing a reliable source of RNA for molecular characterization, and ensuring sample safety.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, Krambrich et al [45] observed the detection of the Sindbis, Chikungunya, and Japanese encephalitis viruses, which remained detectable when stored in the infected FTA card at 4 • C and 25 • C over a 30-day period but degraded rapidly at 37 • C. However, our study discerned an inverse correlation between the detection limit and storage duration, particularly pronounced for AIV and NDV, as detailed in Tables 3 and 4. Furthermore, the detection limit in our study accurately paralleled the actual virus titer on the FTA card and could also depict the detected titer, aligning with the reported findings of Rattanamas et al [46]. This alignment with previous research emphasizes the reliability of our study's findings and underscores the practical implications for virus detection and storage strategies.…”
Section: Discussionsupporting
confidence: 89%